Does predictability matter? Effects of cue predictability on neurocognitive mechanisms underlying prospective memory - Cona, Giorgia; Arcara, Giorgio; Tarantino, Vincenza; Bisiacchi, Patrizia S. (Frontiers in Human Neuroscience, 2015)
Prospective memory (PM) represents the ability to successfully realize intentions when the appropriate moment or cue occurs. In this study, we used event-related potentials (ERPs) to explore the impact of cue predictability on the cognitive and neural mechanisms supporting PM. Participants performed an ongoing task and, simultaneously, had to remember to execute a pre-specified action when they encountered the PM cues. The occurrence of the PM cues was predictable (being signalled by a warning cue) for some participants and was completely unpredictable for others. In the predictable cue condition, the behavioural and ERP correlates of strategic monitoring were observed mainly in the ongoing trials wherein the PM cue was expected. In the unpredictable cue condition they were instead shown throughout the whole PM block. This pattern of results suggests that, in the predictable cue condition, participants engaged monitoring only when subjected to a context wherein the PM cue was expected, and disengaged monitoring when the PM cue was not expected. Conversely, participants in the unpredictable cue condition distributed their resources for strategic monitoring in more continuous manner. The findings of this study support the most recent views – the ‘Dynamic Multiprocess Framework’ and the ‘Attention to Delayed Intention’ (AtoDI) model – confirming that strategic monitoring is a flexible mechanism that is recruited mainly when a PM cue is expected and that may interact with bottom-up spontaneous processes.